Investigating uncertainty in global hydrology modelling - Smith, Katie A. (2016)
As projections of future climate raise concerns over water availability and extreme hydrological events, global hydrology models are increasingly being employed to better understand our global water resources and how they may be affected by climate change. Being a relatively recent development in hydrological science, global hydrology modelling has not yet undergone the same level of assessment and evaluation as catchment scale hydrology modelling. Until now, global hydrology models have presented just one deterministic model output for use in scientific research. Recently, multi-model ensembles have compared these outputs for different global models, but this has been done prematurely as the uncertainties within individual models have yet to be understood.